A Bookshelf in Public Health, Medical Care, and Allied Fields - La Rocco, August (1972)
This bibliography of nonserial publications consists of 610 annotations. It is intended as a guide to the development of a collection for librarians and for health professionals in research and education. References are mostly to publications from 1960. Titles are in English. Both primary and secondary sources are cited.